Opresión, racismo y enajenación en Chile/Chiloé. Una lectura intercultural desde el currículum - Meza Bravo, Miguel (2023)
The reflections in this work arise within the framework of a pedagogical experience in the subjects of History and Language and Culture of Indigenous Peoples at a rural school in southern Chiloé Island (Quellón), a territory characterized by maintaining a series of ancient indigenous practices. In this sense, this work falls within the methodological proposal of Action Research, as it is a self-reflection on a specific social practice within the context of a historical phenomenon in a particular time and physical space. It proposes to carry out a critical and intercultural contextualized analysis of the educational context in question, with special consideration given to the analysis of the curriculum, which is conceived as a social construct resulting from power relations among individuals and society throughout history. From this perspective of the curriculum (as a social and historical product) and through the use of analytical categories from various strands of critical and intercultural theory, the aim is to delve deeper into the comprehensive analysis of this social phenomenon or process. In this sense, by analyzing technical rationality, Eurocentric rationality, hidden curriculum, subjective factors, identity, and alienation, the objective is to understand the connection between the production of a specific subjectivity linked to the educational experience of the curriculum imposed by modern institutions and the socio-historical conditions of Chilote society. Considering that this work is still in progress, we can provide some initial synthesis and preliminary conclusions. For example, at the beginning of the 20th century, indigenous communities on Chiloé Island suffered a profound undermining of their identity, memory, and knowledge like never before in thousands of years of existence in the territory. In this regard, for these peoples, their late inclusion in the modern national life of the Chilean state implied the absolute alienation of the Mapuche-Williche identity, leading to a dialectic of Inclusion/Exclusion. We propose that the development of educational institutions (with a particular curriculum concept), along with the historical, social, and economic development imposed by large capital, functioned in an interrelated manner. This resulted, from the educational perspective, in the internalization of technical and Eurocentric rationality into the identity of the population, undermining the importance of the history and memory of the ancestral indigenous peoples of the territory (Williche and Chono) and, as a consequence, the alienation and degradation of indigenous identity. On the other hand, it led to the internalization of capitalist and modern values, legitimized by the state's institutions, as desirable and positive. We believe that this work can make a contribution on various levels, both in the academic, professional, and social spheres. Firstly, it brings academia closer to the reality in which the curriculum is experienced in schools. Additionally, developing reflections on educational practice from within the educational practices themselves becomes a fundamental resource for school teachers. Lastly, we argue that researching and generating knowledge about a specific social issue, in this case, the oppression of indigenous peoples and the alienation of their identity, enables the production of political tools for understanding and potential transformation toward a better life.